Linoleic acid, α-linolenic acid, and monolinolenins as antibacterial substances in the heat-processed soybean fermented with Rhizopus oligosporus. Issue 6 (2nd June 2020) - Kusumah, Dewi; Wakui, Misaki; Murakami, Mai; Xie, Xiaonan; Yukihito, Kabuyama; Maeda, Isamu
ABSTRACT: Antibacterial activities against Staphylococcus aureus and Bacillus subtilis were found in an ethanol fraction of tempe, an Indonesian fermented soybean produced using Rhizopus oligosporus . The ethanol fraction contained free fatty acids, monoglycerides, and fatty acid ethyl esters. Among these substances, linoleic acid and α-linolenic acid exhibited antibacterial activities against S. aureus and B. subtilis, whereas 1-monolinolenin and 2-monolinolenin exhibited antibacterial activity against B. subtilis . The other free fatty acids, 1-monoolein, monolinoleins, ethyl linoleate, and ethyl linolenate did not exhibit bactericidal activities. These results revealed that R. oligosporus produced the long-chain polyunsaturated fatty acids and monolinolenins as antibacterial substances against the Gram-positive bacteria during the fungal growth and fermentation of heat-processed soybean. Graphical abstract: : Tempe contains linoleic and α-linolenic acids, which are bactericidal against S. aureus and B. subtilis, and monolinolenins, which are bactericidal against B. subtilis .